Pesan Dalam Foto Brassai Berjudul Bijou Of The Montmatre Cabarets - Astiti, Anin (Capture : Jurnal Seni Media Rekam, 2011)
Brassai works titled "Bijou" of the Montmartre cabarets is very interesting theory revealed by semiotics. The photo is one of the works in the project Brassai Paris by Night is doing to document Paris at night. On the work found several signs that can be described with particular semiotic theory of semiotics Barthes. "Bijou" of the Montmartre cabarets is a representation of the nightlife in Paris which is illustrated by the figure of an old woman who works as an entertainer with a background in a nightclub atmosphere. The visual expression achieved with the proper use of photographic techniques by Barthes either through the use of natural light and a standard lens.Â Key words: photography, sign, semiotica